2009
DOI: 10.1111/j.1476-4431.2009.00480.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body position on the arterial partial pressures of oxygen and carbon dioxide in spontaneously breathing, conscious dogs in an intensive care unit

Abstract: PaO(2) was significantly higher when animals were positioned in sternal recumbency compared with lateral recumbency, predominantly due to improved pulmonary oxygen uptake (decreased A-a difference) rather than increased alveolar ventilation (decreased PaCO(2)). Patients with hypoxemia (defined as PaO(2)<80 mm Hg) in lateral recumbency may benefit from being placed in sternal recumbency. Sternal recumbency is recommended to improve oxygenation in hypoxemic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…A potential reason for the high SO 2 % observed may be that the high oxygen affinity Hb (low P 50 ) found in the Greyhound makes Greyhound Hb more likely to remain bound to oxygen, therefore leading to the higher than expected SO 2 %. It is also important to note that, although this instrument b is widely used in hospitals and emergency practices, 26–28 no validation for its use in dogs has been reported. The only parameter that has been validated in vitro is SO 2 % 29 …”
Section: Discussionmentioning
confidence: 99%
“…A potential reason for the high SO 2 % observed may be that the high oxygen affinity Hb (low P 50 ) found in the Greyhound makes Greyhound Hb more likely to remain bound to oxygen, therefore leading to the higher than expected SO 2 %. It is also important to note that, although this instrument b is widely used in hospitals and emergency practices, 26–28 no validation for its use in dogs has been reported. The only parameter that has been validated in vitro is SO 2 % 29 …”
Section: Discussionmentioning
confidence: 99%
“…Given that most veterinary patients are already ventilated in the prone position, it is unclear if changing to supine would have the same effect. It has been previously shown that prone positioning provides the best oxygenation for dogs, but this study was performed in spontaneously breathing dogs, and placement into supine position was not studied 9 .…”
Section: Resultsmentioning
confidence: 99%
“…Respiratory compromise was briefly noted, as evidenced by transient hypoxaemia, PaO 2 80 mmHg (FiO 2 0.21) with an A:a gradient of 32 and an increased respiratory rate. This may indicate respiratory compromise caused by bronchorrhea and/or bronchospasm associated with anaphylaxis or atelectasis resultant from recumbency . Although the dog was not intubated at the time of vomiting, aspiration was not considered likely because the hypoxaemia was transient as evidenced by a normal A:a gradient 6 h following the reaction (Table ).…”
Section: Discussionmentioning
confidence: 99%